The Effect of Smart Card Media Utilization on Learning Outcomes of Mathematics Subjects for Grade 1 Elementary School: Pengaruh Pemanfaatan Media Smart Card Terhadap Hasil Belajar Mata Pelajaran Matematika Kelas 1 SD - Wahyu Ashari; Tri Linggo Wati (Academia Open, 2022)
Media helps the learning process to meet the Minimum Completeness Criteria. This research is quantitative with the reliability test results of the smart card capability test of 10 items. Stated reliable r Alpha = 7.57. The results of the data obtained, it is known from the significance value of the calculation of the normality test is 0.01 from the results of the pretest data on 25 students and 0.71 from the results of the post-test data on 25 students. From these results, when viewed from the basis of decision making that the normality value> 0.05, it is concluded that the data is normally distributed. From the results of t arithmetic, it can be seen that H0 there is no difference in the experimental class and the control class on the use of smart cards in mathematics class 1. There is a difference in the experimental class in the experimental class and the first class on the use of smart card media. Based on the t test with a significant level of 0.01, the result is that if the following test criteria are determined, then Ha is accepted